Le metafore della nozione di dubbio nella lingua italiana - Pastucha-Blin, Agnieszka (Neophilologica, 2007)
The following paper aims at presenting the metaphorical conceptualization of dubbio in the cognitive approach. In basis of the gathered linguistic corpus, which constitutes of information provided by internet sites, the researches evidence the conceptualization of dubbio by transferring some of its aspects to the world of senses. The results demonstrate the complex and coherent cognitive model that describes the concept of dubbio as an entity directly perceptible by means of five physical senses. The dubbio is metaphorized as an actual object, perceptible thanks to the visual, acoustic, tactile, gustatory and olfactory sensibility.